Developing Morally Strong and Intellectually Capable Students: An Islamic Education Model in Senior High School - Zein, Nafisah; Ulfatin, Nurul; Sumarsono, Raden Bambang; Imron, Ali (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
Islamic education in senior high schools (SMA) has a strategic role in shaping the character of the younger generation who are not only intellectually intelligent, but also have strong morals and ethics. Islamic education curriculum management is an important instrument in achieving this goal. This study aims to examine the strategies used by teachers in creating interactive learning that is relevant to students’ daily lives. This research focuses on the optimization of Islamic education curriculum management at SMAN 1 Malang, which is one of the leading schools in Malang City. Using qualitative research methods, data were collected through observation, interviews, and documentation. The collected data were analyzed interactively through three stages: data reduction, data presentation, and conclusion drawing. The results showed that SMAN 1 Malang has successfully optimized the management of Islamic education curriculum through various comprehensive strategies. Among others, strengthening teacher competence, applying active learning methods, using technology in learning, and developing student character. By overcoming various challenges that arise, SMAN 1 Malang is able to improve the quality of Islamic education learning significantly. This finding shows that the strategy applied at SMAN 1 Malang can be used as an example for other schools in an effort to optimize the management of Islamic education curriculum in order to produce a generation that is academically superior, has character, and is ready to face challenges.